Pre-university Measures and University Performance: A Multilevel Structural Equation Modeling Approach - Vista, Alvin; Alkhadim, Ghadah S. (Frontiers in Education, 2022)
This study investigated the relationship between three pre-university measures (high school grade point average, the General Aptitude Test, and the scholastic achievement admission test) and university performance as indicted by (preparatory year and cumulative university grade point average, and graduation). Data from 330,684 undergraduate students from 23 universities across the Kingdom of Saudi Arabia were analyzed using a multilevel structural equation modeling approach. Results indicated that all pre-university measures were consistent in predicting university performance. These findings supported previous results that pre-university measures performance predict eventual performance at the university, including performance at the preparatory year, and whether the student stays regular and eventually completes university studies. These results have implications for the importance of the pre university measures in predicting university eventual success and graduation and this study adds to the body of work that can inform further cost-benefits of the pre university measures. For policymakers, these findings suggest that strengthening support during secondary school levels can have positive effects on eventual performance at university.